Pengembangan Kalender Cerita Berbasis Pendidikan Karakter untuk Siswa Sekolah Dasar - Agnesia Leny Perada; Kadek Dewi Wahyuni Andari; Agustinus Toding Bua (STKIP AL HIKMAH SURABAYA, 2020)
This research aimed at developing learning media to assist learners in reading and writing activities and to instill character values. This was a research and development study. This study reffered to the research and development model by Borg and Gall and Sugiono. The were 7 stages performed in this study: (1) potential and problems, (2) data collection, (3) product design, (4) product validation, (5) product revision, (6) initial fields trials, and (7) trial run. Data were collected through interviews, validation sheets, and student questionnaire responses. The story calendar assessment results were obtained from validation sheet and student response questionnaire. The validation results showed that 87.5% was given by linguists, 88.89% by literature experts, 82.5% by media experts, 87.5% by design experts, and 98.2% by educational practitioners. The results of student responses in the initial field trial was 99.25% and in the use trial was 96.92%. Based on these results, the media of story calendar which was based on character education was suitable for use in the learning process.